Medium optimization for the production of the aroma compound 2-phenylethanol using a genetic algorithm - Etschmann, M.M.W; Sell, D; Schrader, J (Journal of molecular catalysis. B, Enzymatic, 2004)
Using a genetic algorithm, 13 medium constituents and the temperature were varied to improve the bioconversion of l-phenylalanine (l-phe) to 2-phenylethanol (2-PE) with Kluyveromyces marxianus CBS 600. Within four generations plus an additional temperature screening, corresponding to 98 parallel experiments altogether, a maximum 2-PE concentration of 5.6g/l, equivalent to an increase of 87% compared to the non-optimized medium was obtained. The vitamin content of the medium had to be raised significantly.